Keterbukaan Informasi Publik dan Partisipasi Bermakna dalam Perumusan RTRW Kalimantan Barat 2024–2044 - Ivan Wagner; Weni Sentia Marsalena; Syarif Muhammad Ridho Rizki Maulufi Alkadrie (Diktum: Jurnal Ilmu Hukum, 2025)
The implementation of Public Information Disclosure (Keterbukaan Informasi Publik/KIP) and public participation in the formulation of the Regional Spatial Plan (RTRW) of West Kalimantan Province for 2024–2044 continues to face structural and procedural challenges. Although Law Number 14 of 2008 on Public Information Disclosure guarantees the right of access to information, the practice of drafting the RTRW reveals a significant gap between legal norms and their empirical implementation. This study employs an empirical legal method with a socio-legal approach, conducted from January to August 2024, involving 18 informants comprising local government officials, members of the Regional House of Representatives (DPRD), academics, and representatives of civil society. Data were collected through in-depth interviews, document analysis, and participatory observation, and were examined using Arnstein’s Ladder of Citizen Participation as an analytical framework. The findings demonstrate that proactive disclosure of strategic documents, particularly the Strategic Environmental Assessment (KLHS) and the draft Regional Regulation (Raperda), remains inadequate through official governmental channels. Public participation mechanisms tend to be procedural and formalistic, falling short of the principles of public information disclosure, Free, Prior and Informed Consent (FPIC), and meaningful participation. Previous studies have not specifically examined the implementation of public information disclosure in the formulation of regional spatial planning regulations using Arnstein’s participatory framework, thereby leaving an empirical gap at the subnational level. The novelty of this research lies in integrating normative analysis of public information law with an empirical assessment grounded in participation theory to determine the actual degree of participation. Formally, participation reaches the level of consultation (tokenism), yet substantively it descends into therapy or manipulation (non-participation). These findings underscore the urgency of restructuring spatial governance to ensure substantive transparency and participatory legitimacy in regional policymaking.